Mussel-inspired epoxy-dopamine polymer as surface primer: The effect of thermal annealing treatment for enhanced adhesion performance both at dry and hot/wet conditions. (6th April 2022) - Li, Xiaoting; Zhang, Yinyu; Li, Gaoming; Zhao, Xiuli; Wu, Yeping
Abstract: Adhesive protein secreted by marine mussel have strong wet adhesion on various surfaces, which inspires the research of catechol-functional polymer to develop green surface treatment agent and excellent adhesives materials. Herein, we designed a green and simplified route to synthesis epoxy dopamine polymer (EP-DA) containing the structure of L-3, 4-dihydroxyphenylalanine (DOPA) in mussel adhesive protein through epoxy-amine ring opening reaction as a new surface treatment agent. The enhanced adhesion properties of the surface primer before and after thermal annealing treatment (130 °C for 6 h under vacuum) were investigated both at dry and hot/wet conditions. The lap shear strength of EP-DA coated stainless steel (SS) increased from 9.72 MPa to 13.26 MPa compared with untreated substrates, and further increased to 20.02 MPa after EP-DA thermal annealing treatment (EP-DA-an). Moreover, the adhesion strength of EP-DA-an treated SS maintained as high as 16.45 MPa after immersed in water at 50 °C for 40 days, while the adhesion strength of untreated and EP-DA treated SS dropped to nearly zero. For the first time, it was proved that the annealing treatment and DA structure have a significant synergistic effect on the improvement of the hygrothermal ageing resistance of adhesion, indicating that EP-DA polymer can be used as an excellent primer for adhesion. Graphical abstract: Image 1 Highlights: Dopamine modified epoxy polymer as a primer for bonding. Thermal annealing treatment of the primer enhanced the adhesion strength. Primed specimens showed much better resistant to hot water than untreated and epoxy primed specimens.